Comparative characteristics of plant protection against copper and sulphur influence - Eugen Skura; Romina Koto; Erinda Lika; Shpend Shahini; Fatbardh Sallaku (Наукові горизонти, 2023)
Efficient agriculture provides not only food security but also improves the economy of the country. Despite the existence of different types of agricultural production (traditional or organic), plant protection is currently a necessary component. Copper and sulphur are effective against pests and improve the quality and quantity of crops, but are toxic and harm the environment, biodiversity, and human health. The purpose of the study is to investigate the current situation regarding the use of copper and sulphur in plant protection in the Republic of Albania and other countries of the Balkan Peninsula and Europe. Theoretical and empirical research methods were used in the study. As a result, it was determined that the studied elements were actively used in different European countries, both in traditional and organic agriculture. There is a tendency to reduce the norms of use, and in some countries – the removal of these chemical elements from plant protection programmes. The paper includes a comparative characteristic of the use of copper and sulphur and a survey among Albanian agricultural producers on the use of preparations based on these elements. It is established that in the republic, copper and sulphur are actively used mainly in the form of herbicides and fungicides. They are used on vegetable and fruit crops, as well as grapes and olives. There is a problem of informing producers about the negative impact of copper and sulphur on the environment and human safety, as well as control by the state. The practical significance of the study lies in the analysis of the current situation of copper and sulphur use in Albania and in the identification of ways to change it for the better